Ultrasonography of simple intratesticular cysts: a 13 year experience in a single centre - Coker Charles; Khan Khalid; Maan Zeshaan N; Misra Saumya; Al-Jabri Talal; Thompson Phil (BMC, 2011)
Abstract Objectives Simple intratesticular cysts are being reported more commonly due to the wider use of scrotal ultrasonography however, their management remains unclear. Treatment has included enucleation, radical orchidectomy (over fear of an associated malignancy) and a more conservative approach with serial ultrasonography (if a neoplastic cyst is clearly ruled out). In view of the benign nature of such cysts, even serial ultrasonography may be unnecessary. We evaluate the presentation, diagnosis and management of ultrasound-detected simple intratesticular cysts over a 13-year period. Methods Between May 1994 and August 2007, 24 men were found to have simple intratesticular cysts on scrotal ultrasonography. Records were analysed retrospectively to identify the clinicoradiologic findings and the management. Results Median follow up was 29.5 months (range 4 - 108 months). Only one patient became symptomatic with a cyst which increased in size by 13 mm over 15 months. Orchidectomy performed at the patient's request confirmed a benign simple cyst. Conclusions In our series, a significant change in size of the cyst with accompanying symptoms was observed in one case only. Asymptomatic patients with simple intratesticular cysts without associated features of bias towards malignancy can be discharged without need for further follow-up.